2018
DOI: 10.1007/s00894-018-3692-x
|View full text |Cite
|
Sign up to set email alerts
|

Benchmark of different charges for prediction of the partitioning coefficient through the hydrophilic/lipophilic index

Abstract: A few different theoretical methods for assigning the partial atomic charges were benchmarked for calculation of the hydrophilic/lipophilic index (HLI). The coefficients were selected to produce the best correlation of the HLI values with the experimental octanol-water partition. Different parameters were checked in calculations of partial charges to get the best performance of the HLI values obtained. Thus, four partitioning schemes (Coulson, Mulliken, Merz-Kollman, Ford-Wang) were benchmarked for calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 68 publications
0
10
0
1
Order By: Relevance
“…Examples of the usage of RM1 together with other quantum chemical methods include: calculations of the enthalpy of formation of tensile cyclic molecules in condensed phase by employing electrostatic potentials and QSPR; 307 calculations of the linear free energy studies of the rates of reductive defluorination of a set of perfluorinated alkyl compounds; 301 a conformational investigation of the oxime compounds toxogonine, trimedoxime bromide (TMB-4) and obidoxime (HI-6); 341 energy and structural properties of the acid-catalyzed aromatic epoxide ring openings; 344 a benchmark computational study of the proton transfer reaction cysteine-histidine in protein environment; 325 a QM/MM evaluation of the chemical glycobiology; 318 a study of the chemical reactivity in a virtual environment; 317 a benchmark investigation of the geometries of the ground-state of p-type semiconducting molecules that exhibit different polarities; 316 evaluation of the electrostatic potentials on the docking precision of cyclin-dependent kinase 2 protein; 315 and a benchmark study in order to investigate aspects of the reaction to protonate glycine by an ion-molecule collision. 345 RM1 was also used in many studies to predict physicochemical and optical properties, such as activity coefficients, 346 reaction energies, 310,343 energy profiles of reactions, 317,329 and cysteine-histidine proton transfer reactions in different environments. 91,309,316,318,323,344 In most of these studies, RM1 was used to obtain the ground state geometries and other molecular properties, either in gas phase, or in solution (using any solvation model).…”
Section: Comparison Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Examples of the usage of RM1 together with other quantum chemical methods include: calculations of the enthalpy of formation of tensile cyclic molecules in condensed phase by employing electrostatic potentials and QSPR; 307 calculations of the linear free energy studies of the rates of reductive defluorination of a set of perfluorinated alkyl compounds; 301 a conformational investigation of the oxime compounds toxogonine, trimedoxime bromide (TMB-4) and obidoxime (HI-6); 341 energy and structural properties of the acid-catalyzed aromatic epoxide ring openings; 344 a benchmark computational study of the proton transfer reaction cysteine-histidine in protein environment; 325 a QM/MM evaluation of the chemical glycobiology; 318 a study of the chemical reactivity in a virtual environment; 317 a benchmark investigation of the geometries of the ground-state of p-type semiconducting molecules that exhibit different polarities; 316 evaluation of the electrostatic potentials on the docking precision of cyclin-dependent kinase 2 protein; 315 and a benchmark study in order to investigate aspects of the reaction to protonate glycine by an ion-molecule collision. 345 RM1 was also used in many studies to predict physicochemical and optical properties, such as activity coefficients, 346 reaction energies, 310,343 energy profiles of reactions, 317,329 and cysteine-histidine proton transfer reactions in different environments. 91,309,316,318,323,344 In most of these studies, RM1 was used to obtain the ground state geometries and other molecular properties, either in gas phase, or in solution (using any solvation model).…”
Section: Comparison Studiesmentioning
confidence: 99%
“…They stated: "It was concluded that RM1 methodology better agrees with γ experimental results for TPA oligomers". Another recent benchmark investigation was carried out by Fizer et al 346 that evaluated different charges in order to predict partitioning coefficient through the hydrophilic/lipophilic index. The authors concluded that: "The performance order of suitable semiempirical methods is the same as for the semiempirical Mulliken charges: PM7 > RM1 > PM6-D3H4 ≥ PM6 > PM3".…”
Section: Comparison Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…9 It was demonstrated that entropy may contribute to significant changes in the solubility of the nanocrystalligands complexes. 10,11 In addition, in the polar phase, the solute polarizability 12 and polarity 13 are much more sensitive to the partition coefficient. The delicate balance between the entropy and the polarity in transporting small drug from phase of water to lipid was also revealed by our molecular dynamics (MD) simulations with both implicit and explicit polarization models .…”
mentioning
confidence: 99%
“…Метою даного дослідження було провести детальний аналіз структурних особливостей продукту реакції. Цей вибір обумовлений нашими попередніми дослідженнями, де було встановлено, що РМ7 добре моделює геометрію азольних систем [10,11], та є надзвичайно корисним для дослідження реакційної здатності [12] та коефіцієнту розподілу logP [13].…”
unclassified